Upper Triassic (Norian) hypercalcified sponges from the Musandam Peninsula (United Arab Emirates and Oman) - Senowbari-Daryan, Baba; Maurer, Florian (Facies, 2008)
Supercalcified sponges, including sphinctozoans, inozoans, chaetetids, spongiomorphids, occurring in Upper Triassic (Norian-Rhaetian) shallow-marine limestones of Musandam Mountains in United Arab Emirates (UAE), are described. The following taxa were determined: sphinctozoans: Hajarispongia osmani Senowbari-Daryan and Yancey, Nevadathalamia arabica n. sp., Nevadathalamia conica n. sp., anthalamia milahaensis n. sp., Iranothalamia incrustans (Boiko), Cinnabaria regularisn. sp.; inozoans: Cavsonella triassica n. sp., Molengraaffia regularis Vinassa de Regny, Peronidella? sp., Circopora cf. caucasica Moiseev, Circopora? sp.; spongiomorphids: Spongiomorpha sp.; chaetetids: Lovcenipora chaetetiformis Vinassa de Regny, Lovcenipora musandamensis n. sp., Lovcenipora sp., chaetetid sponge gen. et sp. indet. The most abundant sponge in the studied material is Nevadathalamia arabica n. sp. The described sponge association of the Arabian shelf (Musandam Mountains) shows close affinity to the sponge association known from age-equivalent terranes in the Panthalassa Ocean (Sonora Mountains in Mexico; Pilot Mountains in Nevada, USA), but is remarkably different from sponge associations in carbonates bordering the Tethys. This difference goes along with the biogeography of wallowaconchid bivalves and is most likely attributed to climatic, palaeogeographic or oceanographic factors. © Springer-Verlag 2008.
UnivIS-Import:2017-11-07:Pub.2008.nat.dgeo.IGM.LP.uppert
Keywords: Chaetetida; Inozoa; Norian; Oman; Sphinctozoa; Sponges; Spongiomorphida; Triassic; United Arab Emirates